The inhibition of Carica papaya leaves extract on the corrosion of cold worked and annealed mild steel in HCl and NaOH solutions using a weight loss technique - Nwigwe, Samuel Uzoma; Umunakwe, Reginald; Mbam, Stephen Ogbonna; Yibowei, Moses; Okon, Kooffrey; Kalu-Uka, Godwin (Engineering and Applied Science Research, 2019)
The current work investigates the corrosion inhibition of cold worked and annealed mild steel in 0.5 M HCl and 0.5 M NaOH solutions with Carica papaya leaf extract as an inhibitor. The as-received diameter of the mild steel rods was 4.42 mm before some of them were cold drawn to 3.35 mm wire bars. Rods that were 30 mm in length were cut from the as-received, cold worked and annealed samples. The cut samples were thoroughly pickled, dried and weighed before they were suspended in an aggressive media that contained the inhibitor as well as in the media without inhibitor. The samples were examined on the 3rd, 5th, 7th, 10th, 12th, 14th and 17th days, and then, pickled, dried and reweighed. In the 0.5 M HCl solution without inhibitor, maximum corrosion rates of the as-received and cold worked samples were reported on the 5th day, and their values were 1.0x10-4 and 1.3x10-4 g/cm2h, respectively. The maximum corrosion rate of the annealed sample was reported on the 12th day and its value was 5.9x10-5 g/cm2h. The extract was able to reduce the maximum corrosion rates of the as-received, cold worked and annealed samples in 0.5 M HCl solution by 54.1 %, 42 %, and 23.1 %, respectively. Similarly, in a 0.5 M NaOH solution without inhibitor, maximum corrosion rates of the as-received and cold worked samples were reported on the 5th day. Their values were 7.0x10-5 and 8.8x10-5 g/cm2h, respectively. The maximum corrosion rate of the annealed sample was reported on the 12th day and its value was 4.1x10-5 g/cm2h. The inhibitor reduced the maximum corrosion rates in a 0.5 M NaOH solution by 53.8 %, 51.4 % and 33.3 % for the as-received, cold worked and annealed samples respectively. The corrosion rates of all the samples were reduced in the media that contained the inhibitor.